A Review of Recent Advancements in Geophysical Technologies and Their Implications for Mineral and Hydrocarbon Exploration - Haritha, K. (Bumi Publikasi Nusantara, 2023)
Geophysical technologies have undergone significant advancements in recent years, providing new insights into the subsurface and enhancing the exploration of mineral and hydrocarbon resources. This review paper presents an overview of recent advancements in geophysical technologies and their implications for mineral and hydrocarbon exploration. The paper begins with a discussion of electromagnetic, seismic, gravity and magnetic, ground penetrating radar, and borehole geophysical methods, highlighting their respective advancements. The paper then examines the implications of these advancements for mineral and hydrocarbon exploration, including improved resolution and accuracy of geophysical data, cost-effective exploration in remote and challenging environments, a better understanding of subsurface structures and geology, identification of new mineral and hydrocarbon resources, and reduction of exploration risk and improved economic viability. Case studies are presented to demonstrate successful applications of geophysical technologies in mineral and hydrocarbon exploration. Finally, the paper discusses the challenges and future directions for research and development, including limitations of geophysical technologies, integration with other exploration methods, emerging geophysical technologies, and their potential for mineral and hydrocarbon exploration.